Treatment of Oil-Water Mixture Using Illite Clay Mineral - Turak, Fatma; Afsar, Hueseyin (SPRINGER, 2009)
The aim of this work was to study the simultaneous effect of amount of clay, activation temperature, contact time, pH, and size of the adsorbent on the retention of oil-grease thermally activated illite by adsorption. The values obtained for the percentage of oil-grease removed ranged from 93.87% for 110 degrees C up to 66.73% for 900 degrees C. The adsorption experiment showed surface that the stronger heat treatment the most effective adsorption of oil-grease.
Keywords: Adsorption; clay; illite; x-ray diffraction; WASTE-WATER; Biochemistry & Molecular Biology; Chemistry